Effects of aggregates' shape properties on the packing structure of porous asphalt mixture (PAM) by utilising designed aggregates - Yoong, Daryl Wen Kiat (Nanyang Technological University, 2020)
In natural aggregates, the particle shape is dependent on the nature of the rock and crushing process which affect the properties of PAM. However, due to the lack of variation in the shape properties in the natural aggregates, the relationship between the packing structure of PAM and specific shape properties is not well established. Therefore, the project aims to study the relationship between the packing structure of PAM and aggregate shape properties (sphericity) by introducing artificially-designed metal aggregates of various shapes such as sphere, cube and cylinder.